Impact of Social and Psychological Factors on Conspicuous Consumption of Young Financial Professionals in Anhui Province, China - Wang, Dan; Arayachosagul, Naaphitsara (วารสารนวัตกรรมการศึกษาและการวิจัย, 2026)
This study investigates the impact of social and psychological factors on conspicuous consumption among young financial professionals in Anhui Province, China. Data were collected through a large-scale survey, and the quantitative analysis was conducted using Structural Equation Modeling (SEM) to test hypothesized relationships. The results indicate that brand symbolism and reference group value expression have significant positive effects on conspicuous consumption, whereas the traditional Chinese value of frugality has a negative effect. Psychological factors also play a critical role: self-congruity and self-esteem both positively influence conspicuous consumption and serve as mediators in the relationships between social factors and conspicuous consumption. Specifically, self-congruity mediates the effects of brand symbolism and reference group value expression, while self-esteem mediates the effects of brand symbolism, reference group value expression, and frugality. Complementing these findings, qualitative interviews with young professionals provided deeper insights into the symbolic meanings of brands, the tension between modern consumerism and traditional frugality, and the ways in which self-perception shapes consumption choices. Together, these results contribute to the understanding of conspicuous consumption in the Chinese cultural context and provide practical implications for policymakers and marketers.